A new chitinase-D from a plant growth promoting Serratia marcescens GPS5 for enzymatic conversion of chitin. (November 2016) - Vaikuntapu, Papa Rao; Rambabu, Samudrala; Madhuprakash, Jogi; Podile, Appa Rao
Graphical abstract: Highlights: Characterized a new single modular chitinase, Sm ChiD from Serratia marcescens GPS5. Without accessory binding domains Sm ChiD hydrolyzed polymeric chitin substrates. Sm ChiD exhibited chitobiase and transglycosylation activity on chitooligosaccharides. Transglycosylation activity of Sm ChiD can be used for synthesis of long chain CHOS. Chitobiase activity of Sm ChiD can be used for producing GlcNAc from polymeric chitin. Abstract: The current study describes heterologous expression and biochemical characterization of single-modular chitinase-D from Serratia marcescens ( Sm ChiD) with unprecedented catalytic properties which include chitobiase and transglycosylation (TG) activities besides hydrolytic activity. Without accessory domains, Sm ChiD, hydrolyzed insoluble polymeric chitin substrates like colloidal, α- and β-chitin. Activity studies on CHOS with degree of polymerization (DP) 2–6 as substrate revealed that Sm ChiD hydrolyzed DP2 with a chitobiase activity and showed TG activity on CHOS with DP3–6, producing longer chain CHOS. But, the TG products were further hydrolyzed to shorter chain CHOS with DP1–2 products. Sm ChiD with its unique catalytic properties, could be a potential enzyme for the production of long chain CHOS and also for the preparation of efficient enzyme cocktails for chitin degradation.